Pengaruh Pengalaman Kerja, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Satgas Gerdema Pada Dinas Pemberdayaan Masyarakat Dan Desa Kabupaten Malinau - Charles, Oktrianus; Millan, Alston; Balang, Johni (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2020)
The purpose of this study was to determine the effect of work experience, work motivation and work environment on the performance of the Gerdema task force. In this study data were collected by interview, observation and questionnaire on 50 respondents. The analysis used includes test data instruments (validity test and reliability test), multiple linear regression analysis, classic assumption test (normality test, multicollinearity test, heteroscedasticity test), and hypothesis testing (f test, t test, coefficient of determination). From the results of the analysis using regression, it can be seen that the variables of work experience, work motivation and work environment all have a positive influence on the performance of the Gerdema task force. From the t-test results obtained from work experience, work motivation and work environment, all have a significant influence on the performance of the Gerdema task force.Â Keywords: work experience, work motivation, work environment, performance, GerdemaÂ